Association between glycemic control and autonomic dysfunction: A cross-sectional study in type 2 diabetes mellitus patients - Jibin Simon; Srinivasa Guptha L.R.; Jagadeesan M.; Sharan Bose (Romanian Medical Journal)
Background. Orthostatic hypotension (OH) stands as one of the initial indications of cardiac autonomic dysfunction in diabetic individuals. Our objective is to assess the prevalence of OH across different degrees of diabetes. Materials and methods. This study is a cross-sectional investigation conducted at a tertiary care center. After obtaining ethical committee clearance and informed consent, 150 individuals aged above 50 years were recruited for this study. 50 of them had normal HbA1c levels, 50 with HbA1c levels between 7-8 and another 50 individuals with more than 8 HbA1c values. Results. The duration of diabetes exhibited a strong correlation with HbA1c levels, which was statistically significant (p=0.000). The systolic BP difference in normal, HbA1c 7-8 and HbA1c levels more than 8 were 6.34±1.95, 15.70±8.37 and 17.04±7.74 respectively. The diastolic BP difference in normal, HbA1c 7-8 and HbA1c levels more than 8 were 4.00±1.42, 7.72±5.26 and 12.22±7.77. These results were found to be statistically significant (p=0.000). Conclusion. OH serves as an ominous sign in diabetic patients, indicating a poor prognosis. Individuals with OH are at a heightened risk of falls, which in turn, is associated with increased morbidity and mortality. Therefore, it is crucial to prioritize the early detection of autonomic neuropathy, particularly in diabetic patients.